The Legal Certainty of Attorney’s Special Power for Advocates made by a Notary to Conduct a Session in a Religious Court - Rizqiansyah, Arif; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to analyze: The role and authority of a Notary in making a special power of attorney for Advocates who will conduct a trial at the Pekalongan Religious Court. 2) Legal certainty of special power of attorney for advocates made by a notary to conduct a trial at the Pekalongan Religious Court. The approach method used in discussing this problem was a normative juridical approach. Normative juridical is library law research conducted by examining library materials or secondary data. The results of the study: 1) The role and authority of a Notary in making a special power of attorney for Advocates who will conduct a trial at the Pekalongan Religious Court is an attribution obligation carried out based on Article 15 of the Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2014 2004 Regarding the Position of Notary. Attributive authority is an authority that comes from the law. One of these powers is to make a power of attorney. The notary has the authority to make a special power of attorney based on the statements of the witnesses, so that the special power of attorney will have legal force as an authentic deed that is perfect. 2) Legal certainty that a special power of attorney for Advocates made by a Notary to carry out a trial at the Pekalongan Religious Court can be achieved if it meets the requirements in Article 1796 of the Civil Code, which is limited in nature, the legal action can only be carried out by the attorney himself, in addition to the letter must be before a notary. The special power of attorney can be made directly by the parties before a notary, or made by the parties first and then requested for approval by a notary. The legal certainty of a special power of attorney for advocates made by a notary to conduct a trial at the Pekalongan Religious Court is related to the role of a notary in providing legal certainty for his clients. To be able to provide legal certainty, a notary must be guided by the laws and regulations that govern it.